A whole new world : Investigating the use of social media by the Vancouver Public Library to deliver services during the COVID-19 pandemic - Vander Kooy, Sam (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2021)
This poster will present the results of a thematic analysis of the contents of the Vancouver Public Library’s (VPL) Instagram, Twitter, and YouTube feeds throughout the first wave of the COVID-19 pandemic (February 1st to June 30th, 2020) to better understand what types of crisis-related services and information they are providing to the public. This data will also be compared to Instagram, Twitter, and YouTube content from the same time period in 2019 to investigate whether the pandemic has changed VPL’s social media presence in any significant way.